Rainbow Bridge - Hassell, Hank (University Press of Colorado, 2023)
On the morning of August 14, 1909, a small, diverse group including Professor Byron Cummings of the University of Utah, Government Land Office surveyor William Douglass, pioneer archaeologist and trader John Weatherill, and Paiute guide Nasja Begay gazed at the largest structure of its kind in the world-Rainbow Bridge. Their presence marked the official discovery of the magnificent natural bridge, which spans 275 feet and towers 291 feet above the stream bed below it. Of the discovery party, only Nasja Begay had seen the stone arch before; he was one of a probably small number of Paiutes and Navajos, the true modern discoverers, who had visited it. In 1910, an executive order issued under the still fresh Antiquities Act created Rainbow Bridge National Monument, one of the first. This was only the beginning of the Rainbow Bridge historical record. Its fame was soon widespread, but for many years its visitors would be few, their numbers restricted by the long arduous trail around Navajo Mountain to the site. Those few and the tour guides and businesses that emerged to serve them, especially at Rainbow Lodge, were an interesting mix though. The bridge's story included such western figures as trader Louisa Weatherill, wife of John and a Navajo speaker who was the first Anglo to hear of the bridge; Barry Goldwater, who for a time owned and operated Rainbow Lodge; Zane Grey, who wrote about the bridge; and David Brower, the Sierra Club leader who got wrapped up in the intersection of the Rainbow Bridge story with that of Glen Canyon Dam. Its construction and the filling of Lake Powell behind it made Rainbow Bridge a battleground, key territory in the larger war over water and conservation in the West. The remote, hard to reach national monument was supposed to define a limit to Colorado River reclamation but instead was inundated by Lake Powell and the tide of visitors who then could reach the foot of the bridge by boat. Though Rainbow is now easily and frequently visited and National Park Service amenities are in place, access to Rainbow Bridge is still an evolving and controversial issue.